The Cooperation between Indonesia and UNHCR in dealing with Afghan Muslem Refugees (Case Study: Riau Province, 2021-2022). - Renolafitri, Hendrini; Fadhila, Naufal; Dewi, Nevy Rusmarina (State Islamic Institute of Kudus (IAIN Kudus), 2023)
The United Nations High Commissioner for Refugees (UNHCR) plays a crucial role in safeguarding and upholding the rights of refugees worldwide. In November 2021, extensive demonstrations by Afghan refugees occurred across Indonesia, including in Pekanbaru city, Riau Province. These protests persisted on a weekly basis until November 2022. Indonesia served as a transit country for Afghan refugees enroute to their final destination, primarily Australia. The choice of Indonesia as a transit point was driven by its geographical proximity and perceived cultural similarities, particularly in terms of being predominantly Islamic nations. These similarities were expected to foster solidarity and aid in the evacuation process. However, despite these perceived similarities, they found themselves still trapped in Indonesia for an extended period, compelling them to implore UNHCR to expedite the resettlement process. It is noteworthy that Indonesia has not ratified the 1951 Convention, thereby relieving the country of technical responsibility towards international refugees. Nonetheless, given the inevitable nature of the situation, Indonesia and UNHCR must collaborate to effectively address and manage the challenges at hand.